Fracture in polycrystalline diamond. Investigating cracking and toughness behaviour using a miniature double torsion technique - Petrov, Serguei Igorevich (Department of Mechanical Engineering, 2023)
This thesis project studied the crack initiation and controllable propagation of cracks in four grades of polycrystalline diamond (PCD) employing a miniature double torsion (DT) technique. The extremely high stiffness and relatively low toughness of the PCD material make controllable crack propagation and fracture parameter studies very difficult. Therefore, the research project investigated the ability of the DT technique to controllably initiate and propagate cracks, followed by the development of the in-situ SEM miniature DT rig. Development of such a rig permitted the live observation of the cracking process, while capturing the load displacement data. In addition to the in-situ SEM experiments, the fracture process was also observed outside the SEM by digital image correlation (DIC), a full field surface displacement measurement technique. The DIC experiments were performed in both 2D and 3D configurations. The DIC data was processed employing the JMAN routine – a numerical method for the calculation of the J-integral from the DIC measured displacement field. The combination of the DIC and JMAN techniques enabled non-contact characterization of the surface stress intensity around the propagating crack. In addition to the abovementioned techniques, electron backscatter diffraction (EBSD) was employed to investigate the effect of the microstructural features on the behaviour of the various grades of PCD. The miniature DT technique enabled controllable initiation, unloading, analysis and subsequent propagation from “atomically” sharp condition which avoided the notch toughness phenomena. The miniature DT technique enabled clear, repeatable differentiation of the fracture toughness properties of the four grades of PCD studied. In-situ observation of the fracture process, coupled with the fractographic studies of the broken specimens, revealed clear differences in crack propagation behaviour of the specimens with different grain size. The transgranular crack propagation component increased with increasing grain size and contiguity, while the fine grain specimens revealed more secondary damage in the wake of the crack. That is to say that the fine grain specimens revealed a larger fracture process zone (FPZ) than the coarse grain specimens. PCD toughness increased with increasing grain size and increasing contiguity. The non-contact 2D DIC/JMAN experiments characterised the surface stress intensity factor (SIF) around the crack with a good level of accuracy. The non-contact SIF measurements were within 6-8% of those determined by employing the load displacement data and the classical DT formulations. The EBSD characterization of the specimen surface proved very useful in the observation of the crack path as a function of the microstructure. The application of the techniques and methodologies developed and presented in the current research project provide robust new tools in the development of the understanding of the fracture mechanisms in PCD material. The techniques presented can be used to quantify, observe and understand the fracture mechanisms in PCD materials made by new sintering methodologies and new binder/catalyst compositions. The ability to observe and understand the effects microstructural features have on crack resistance, may enable the development of functionally graded materials which employ the principles of biomimicry to develop toughening mechanisms resembling those found in nature.